RUNX1 Germline Mutation in a Patient with Chronic Thrombocytopenia - Yujin Nam; Gyu Min Yeon; Seom Gim Kong (The Korean Society of Pediatric Hematology-Oncology, 2021)
One of the pathophysiologic mechanism of inherited thrombocytopenia is a defect in transcription factors that regulate the expression of multiple genes required for megakaryopoiesis. Runt-related transcription factor 1 (RUNX1) binds to its heterodimeric partner, core binding factor beta (CBFβ), and forms a core binding factor that regulates the expression of various target genes. The association between RUNX1 germline mutations and familial platelet disorder with associated myeloid malignancy was first reported in 1999. Although this disease has various phenotypes and penetration, the most common symptom is a bleeding tendency due to thrombocytopenia and platelet dysfunction. Myelodysplastic syndromes or acute myeloid leukemia may also develop in 35-40% of cases. We identified a heterozygous mutation in the RUNX1 gene using diagnostic exome sequencing in an adolescent with chronic thrombocytopenia. The patient will be followed continuously for hematologic malignancies that may develop in the future. This case illustrates the importance of diagnosing inherited thrombocytopenia to provide adequate follow-up for hematologic malignancies and reduce unnecessary treatment.